A case report: Anesthetic management for open‐heart surgery in a child with congenital insensitivity to pain with anhidrosis. Issue 9 (7th July 2022) - Jiang, Jialong; Wang, Xuefeng; Hu, Jicheng; Wang, Sheng
Abstract: Congenital insensitivity to pain with anhidrosis (CIPA) is a rare disease also known as hereditary sensory and autonomic neuropathy. CIPA is characterized by a lack of pain sensitivity and impaired development of sweat glands. Surgery is required for patients with self‐mutilation and skeletal developmental disorders. Due to the disease's rarity and intricacy, anesthesia poses its challenges. Although there have been a few cases of CIPA patients receiving surgery and anesthesia, the number is very limited. Here, we report a case of a child with CIPA who underwent open‐heart surgery and discuss the anesthetic considerations. We conclude that patients with CIPA undergoing open‐heart surgery require some opioids, that muscle relaxants and volatile anesthetics should be used with extreme caution, and that airway management and temperature control require special attention.